Influencia de dietas alimenticias a diferentes raciones sobre el nivel de hemoglobina y parámetros bioquímicos de Pecari tajacu “sajino”. Centro piloto de crianza de animales silvestres, UNAP- 2024 - Lopez Cachique, Greny Adilia (2025)
The objective of the research was to evaluate the influence of food diets with different rations on the hemoglobin level and biochemical parameters of Pecari tajacu “Sajino”, from the Pilot Center for the Breeding of Wild Animals, UNAP 2024; a quasi-experimental type of research. The sample consisted of the blood of 12 juvenile specimens of both sexes, collected at three times: at the beginning (T0), two months (T1) and four months (T2) after applying the food rations. They were distributed in 3 pens of four individuals per group, providing them with 12 and 14% feed rations and a control group. Samples were processed in automated analyzers. Results: They started (T0), average of hemoglobin 13.00 ± 0.74 g/dL, and the biochemical parameters: Glucose, Cholesterol, Triglycerides and Total Proteins with values within the reference ranges. At the second month (T1), Hb increased in both rations 13.68±0.67 and 13.60 ± 0.52 g/dL. At the end of the study (T2), the average obtained was: Hemoglobin 14.50 ± 7.6 and 13.63 ± 0.35 g/dL; Glucose 129.50 ± 49.13 and 95.50 ± 15.18 mg/dL; Cholesterol 118.25 ± 22.85 and 87.50 ± 12.61mg/dL; Triglycerides 77.25 ± 50.31 and 92.50 ± 43.05 mg/dL; Total Proteins 7.85 ± 0.15 and 7.22 ± 0.92 g/dL. When comparing T1, T2 and the control, significance is observed only for Hemoglobin 14.5 ± 0.76, at the fourth month of study at 12% ration, (p<0.05), the biochemical parameters vary within the reference ranges. Conclusion: The hypothesis raised is not accepted.